Religion in the Age of Globalization and Human Rights: Challenges and Possibilities - Naz, Salma; Raza, Shahid (Pakistan Languages and Humanities Review, 2023)
Religion and globalization has turned into a durable and lithe connection whereas former is enjoying opportunities of progress and expansion in globalized world other side it seems to create resistance for second through challenging its process of fusion or amalgamation of values. In this perspective the upsurge of global human rights has become of convincing indicator of global citizenship. In 1948 International community was evolved some principles for the safeguard of human rights in the shape of Universal Declaration of human Rights. Many scholars believe that human rights is a secular concept and religious communities often had antagonistic attitude towards this concept. But there are many explanations relevance of religions to this notion. Because all religions preach the common values of truth, righteousness, peace, love and patience as well as unity of human being and mutual respect are the core principles of all religions. For this research qualitative research methodology is employed within the post-positivist paradigm and case study method is used. Descriptive, historical and exploratory approaches are used to find the answers of questions. Secondary source is used for data collection. For data analysis analytical technique is applied. This research explores the challenges and possibilities for human rights in the era of globalization in religious perspective and conclude that idea of approachment between religions and human right is conceivable as well as significant particularly in globalized world where concept of global citizenship is flourishing. Some recommendations also presented